A Novel Ensemble Wind Speed Forecasting Model in the Longdong Area of Loess Plateau in China. (10th December 2018) - Fu, Tonglin; Wang, Chen
Abstract : Energy is the lifeline and the base of development of social economy in every country or area. However, with the increasing depletion of fossil energy, it is imperative for business managers and government policy makers to seek and utilize new energy resources for keeping the national economy development sustained, rapid, and healthy. As a new energy resource, wind energy is developing with a high speed in the world for the reasons that it is an abundant natural resource with the characteristics of renewable, low cost, and no pollution. But in reality, forecasting wind speed accurately is continuously a challenging subject in the field of the wind energy development for a long time. In this paper, a novel ensemble wind speed forecasting model based on machine leaning models and hybrid models with data preprocessing technology is proposed to forecast the wind speed effectively in the Longdong area of Loess Plateau in China; numerical results show that the ensemble model has better precision, adaptability, and robustness.